PREVENTION AND MANAGEMENT OF VACCINE HESITANCY: Vaccine Hesitancy - Reis, Christopher A.; Jacobson, Robert M. (Srpski medicinski časopis Lekarske komore, 2026)
Vaccine hesitancy refers to the delay in accepting or refusing vaccines despite the availability of vaccination services. Well-conducted studies and trials reviewed in this article support methods both to prevent and manage vaccine hesitancy. Clinicians should know which vaccines their patients are due to receive and should use every encounter to address this issue. Research shows clinicians’ recommendations increase vaccine uptake. Recommendations that patients perceive as stronger have a greater effect in increasing vaccine uptake. Using presumptive language to phrase the recommendation is more effective than presenting the vaccine conversationally as an option for the patient. When the patient counters the strong recommendation with hesitancy, the clinician should engage the patient with motivational interviewing, perhaps using a four-step process called the “Four A’s”.